Derechos humanos y salud mental en América del Sur Situación de daño psicosocial y procesos de recuperación (crónica inicial). - Riquelme U., Horacio (Cuadernos Médico Sociales, 2022)
This essay deals with the footprint left by civil-military governments on the societies of Argentina, Chile and Uruguay. A systematic study of the reciprocal action between human rights and mental health was carried out. Central questions: 1.- Is it possible to formulate and express, clearly and concisely the characteristics of psychosocial injury? 2.- Is the experiential dimension of those affected and their social environment accessible to understanding? and 3.- Are there promising ways of social and cultural interaction to overcome the effects of integral damage? Elements of psychosocial injury studied: a) Kidnapping and "forced disappearance" of opponents of the regime; b) Systematic torture c) Control and manipulation of the media and d) Exile and forced displacement of people. Based on field and documentary research, this essay gives rise to an analysis of the circumstances of harm in individuals and communities at that time and their treatment in each society.